Does Hyphal‐Tip Ensure the Same Allelic Composition at SSR Loci as Monosporic Isolates of Sclerotinia sclerotiorum?. Issue 6 (17th July 2015) - Lehner, Miller S.; Paula Júnior, Trazilbo J.; Mizubuti, Eduardo S. G.
Abstract: The proper characterization of individual is a basic stage in population genetic studies. In Sclerotinia sclerotiorum, genetic uniformity of an individual can be obtained by isolation of single ascospore; however, hyphal‐tip isolates are commonly used in genetic studies. The aim of this study was to assess whether hyphal‐tip isolates of S. sclerotiorum can be used as surrogate of monoascosporic (monosporic) isolates. Twenty‐eight isolates of S. sclerotiorum were collected from common bean plants with white mold symptoms and were purified by hyphal‐tip or single ascospore. The correspondence between hyphal‐tip and monosporic isolates was assessed through the allelic composition at 10 microsatellite (SSR) loci of the isolates obtained by both methods. For the SSR loci comprised of dinucleotide repeats in 92% of the cases, the difference ( di ) between the amplicon size values for hyphal‐tip and monosporic isolates was no more than one base pair. For the loci comprised of tetra or pentanucleotide repeats in 89% of the cases, di was no more than one base pair. The same allelic profile was found for hyphal‐tip or single ascospore isolates of S. sclerotiorum . When monosporic isolates cannot be easily obtained, hyphal‐tip can safeguard the genotypic identity of S. sclerotioru m isolates.